Kompetensi Kepribadian Guru Perspektif Tafsir Al-Sha’rawi Dalam Q.S. Al-Kahfi Ayat 60-82 - Senata Adi Prasetia; Muhammad Fahmi (LPPM STAI Ihyaul Ulum Gresik, 2020)
This article departs from the concern about the low quality of personality competencies of some teachers. This is reflected in several elementary school teachers in Paiton, Probolinggo and Serang, Banten who molested their students over the past year. This heinous incident was only revealed in January and February 2020. How miris heard it, when a teacher who was supposed to be a person who was seduced and imitated, quite the opposite. This study raised the issue of personality competence of teachers perspective Tafsir Al-Sha'rawi in Q.S. al-Kahfi verses 60-82, its urgency and relevance in the present era. This article is a library research with descriptive-analytical approach, as well as data analysis process using content analysis. The results showed that there are 7 (seven) competencies of teacher personality, namely tawadu' (humble), maintaining adab, firm, spirit, responsible, respecting opinions, and maintaining good relations. The competence of teachers' personalities in the perspective of Tafsir Al-Sha'rawi Q.S. al-Kahfi verses 60-82 is very relevant in the present era so that teachers avoid deviant actions and teachers can fulfill the competencies they should have.